2018
DOI: 10.1177/1120700018759314
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of osseointegration in various types of acetabular implant materials

Abstract: Our study showed that the evaluated implants have good BIC features. Furthermore, based on histomorthometry and histology, Porous tantalum Trabecular Metal (A) and Trabecular Titanium (B) implants exhibit higher BIC with bone tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
1
24
0
4
Order By: Relevance
“…One study by Bondarenko et al showed that osteoporotic bone has worse osseointegration than healthy bone, and also that the implant can have a significant effect on the osseointegration, or bone-implant-contact [36]. In their study the tantalum implant Trabecular Metal ® and the Trabecular Titanium ® showed better osseointegration than the titanium implants Stiktite ® , titanium with Gription ® coating or Tritanium ® [36].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One study by Bondarenko et al showed that osteoporotic bone has worse osseointegration than healthy bone, and also that the implant can have a significant effect on the osseointegration, or bone-implant-contact [36]. In their study the tantalum implant Trabecular Metal ® and the Trabecular Titanium ® showed better osseointegration than the titanium implants Stiktite ® , titanium with Gription ® coating or Tritanium ® [36].…”
Section: Discussionmentioning
confidence: 97%
“…It has also been shown that successful osseointegration can occur with bony attachment that involves substantially less than 100% of the bone/implant interface [33,34] and most of the osseointegration occurs around the acetabular rim, and decreases towards the pole [34,35]. One study by Bondarenko et al showed that osteoporotic bone has worse osseointegration than healthy bone, and also that the implant can have a significant effect on the osseointegration, or bone-implant-contact [36]. In their study the tantalum implant Trabecular Metal ® and the Trabecular Titanium ® showed better osseointegration than the titanium implants Stiktite ® , titanium with Gription ® coating or Tritanium ® [36].…”
Section: Discussionmentioning
confidence: 99%
“…The euthanasia of rats was performed 45 days after surgery by administering a lethal dose of anesthetic (sodium thiopental, 90 mg/kg intramuscularly). This observation period was chosen for the reason that other researchers conducted similar experimental studies on rats in the same period [32], as well as the results of previous study performed by us [28]. Since for this period (45 days) the site of defect is substituted by new formed mature bone.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…All surgeries were performed under general intramuscular anesthesia -ketamine 50 mg/kg. Bilateral ovariectomies were performed in 28 animals in the OVX group according to previously described methodology [28]. For SH group, the ovaries were not removed.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…For SH group, the ovaries were not removed. At 3 months after ovariectomy, when osteoporotic bone changes had developed in OVX group [28], surgery was performed in both groups (OVX & SH) of rats. The skin of the lower extremities was shaved and treated with Betadine® solution.…”
Section: Surgical Proceduresmentioning
confidence: 99%